Effect of SARS-CoV-2 BNT162b2 mRNA vaccine on thyroid autoimmunity: A twelve-month follow-up study - Morita, Shuhei; Takagi, Tomoyuki; Inaba, Hidefumi; Furukawa, Yasushi; Kishimoto, Shohei; Uraki, Shinsuke; Shimo, Naoki; Takeshima, Ken; Uraki, Saya; Doi, Kei; Imagawa, Mitsuyo; Kokawa, Mika; et al. (Frontiers in Endocrinology, 2023)
Objectives: Graves’ disease (GD) has been highlighted as a possible adverse effect of the respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccine. However, it is unknown if the SARS-CoV-2 vaccine disrupts thyroid autoimmunity. We aimed to present long-term follow-up of thyroid autoimmunity after the SARS-CoV-2 BNT162b2 mRNA vaccine. Methods: Serum samples collected from seventy Japanese healthcare workers at baseline, 32 weeks after the second dose (pre-third dose), and 4 weeks after the third dose of the vaccine were analyzed. The time courses of anti-SARS-CoV-2 spike immunoglobulin G (IgG) antibody, thyroid-stimulating hormone receptor antibody (TRAb), and thyroid function were evaluated. Anti-thyroglobulin antibodies (TgAb) and anti-thyroid peroxidase antibodies (TPOAb) were additionally evaluated in thirty-three participants. Results: The median age was 50 (IQR, 38-54) years and 69% were female. The median anti-spike IgG antibody titer was 17627 (IQR, 10898-24175) U/mL 4 weeks after the third dose. The mean TRAb was significantly increased from 0.81 (SD, 0.05) IU/L at baseline to 0.97 (SD, 0.30) IU/L 4 weeks after the third dose without functional changes. An increase in TRAb was positively associated with female sex (β = 0.32, P = 0.008) and low basal FT4 (β = -0.29, P = 0.02) and FT3 (β = -0.33, P = 0.0048). TgAb was increased by the third dose. Increase in TgAb was associated with history of the thyroid diseases (β = 0.55, P <0.001). Conclusions: SARS-CoV-2 BNT162b2 mRNA vaccine can disrupt thyroid autoimmunity. Clinicians should consider the possibility that the SARS-CoV-2 vaccine may disrupt thyroid autoimmunity.